2016
DOI: 10.3389/fendo.2016.00152
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Hepatic Macrophage Populations in Lean and Obese Mice

Abstract: Obesity is a complex metabolic disorder associated with the development of non-communicable diseases such as cirrhosis, non-alcoholic fatty liver disease, and type 2 diabetes. In humans and rodents, obesity promotes hepatic steatosis and inflammation, which leads to increased production of pro-inflammatory cytokines and acute-phase proteins. Liver macrophages (resident as well as recruited) play a significant role in hepatic inflammation and insulin resistance (IR). Interestingly, depletion of hepatic macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 98 publications
2
13
0
Order By: Relevance
“…Interestingly, while we found that Fgf21 ‐/‐ mice had greater hepatic inflammation compared with WT mice fed a HFD for 12 weeks, a longer‐term study found no difference in hepatic inflammation between WT and Fgf21 ‐/‐ mice fed a high‐sucrose HFD for 52 weeks . The increased expression of inflammatory markers in liver of Fgf21 ‐/‐ mice may be due to activation of resident liver macrophages (Kupffer cells) or hepatic infiltration by newly recruited immune cells, both of which occur in obesity . Likewise, the increased expression of inflammatory markers in adipose tissue of Fgf21 ‐/‐ mice may be due to increased cytokine expression by adipocytes themselves, but it is more likely due to an increased presence of inflammatory immune cells .…”
Section: Discussionmentioning
confidence: 63%
“…Interestingly, while we found that Fgf21 ‐/‐ mice had greater hepatic inflammation compared with WT mice fed a HFD for 12 weeks, a longer‐term study found no difference in hepatic inflammation between WT and Fgf21 ‐/‐ mice fed a high‐sucrose HFD for 52 weeks . The increased expression of inflammatory markers in liver of Fgf21 ‐/‐ mice may be due to activation of resident liver macrophages (Kupffer cells) or hepatic infiltration by newly recruited immune cells, both of which occur in obesity . Likewise, the increased expression of inflammatory markers in adipose tissue of Fgf21 ‐/‐ mice may be due to increased cytokine expression by adipocytes themselves, but it is more likely due to an increased presence of inflammatory immune cells .…”
Section: Discussionmentioning
confidence: 63%
“…During obesity, there is an increased number of macrophages infiltration in adipose tissue and liver [ 34 , 35 ]. Increased Lipid influx and accumulation in those organs cause the activation of Kupffer cells (liver resident macrophages) and monocyte-derived macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Increased Lipid influx and accumulation in those organs cause the activation of Kupffer cells (liver resident macrophages) and monocyte-derived macrophages. Moreover, chronic hepatic inflammation leads to fatty liver disease and cirrhosis [ 35 ]. In the current study, macrophages were increased in both liver and fat tissue of HFD-PBS group, which were decreased with reduced inflammatory responses by UTS-001 treatment in both organs.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, the adaptation to latter events is central to preventing dissemination of microbes into peripheral circulation (5,39,40). In obesity, increased intestinal permeability, trafficking of bacteria into the gut lumen and LPS sensing (2,40,41) fuel KC activation and alter their function (42). In this context, activated KCs favor inflammatory responses that contribute to NAFLD pathogenesis (13).…”
Section: Macrophage Subsetsmentioning
confidence: 99%